Exercise Shifts Food Choices Towards Greater and More Immediate Food Consumption (OR08-05-19). (13th June 2019) - Beckford, Safiya; Thayer, Elise; Hubner, Sarah; Kiim, Hyeon Jung; Martin, Alexandra; Cristobal, Alexander; Boron, Julie; Stevens, Jeffrey; Koehler, Karsten
Abstract: Objectives: Laboratory experiments suggest that exercise can modulate appetite regulation and ad libitum food intake, but the impact of exercise on decision making about food remains poorly understood. As such, this study sought to assess the impact of an acute exercise bout on food choices, in particular, the amount and taste preference for immediate and delayed consumption. Methods: 18 male and 23 female participants (age: 22.0 ± 2.6 years; BMI: 23.7 ± 2.5 kg/m 2 ; VO2peak : 37.3 ± 6.2 mL/kg/min) completed two experimental conditions, a 45-min exercise bout at 60% of VO2peak (EX) and a 45-min resting period (R), in a randomized, cross-over design. Electronic questionnaires to assess prospective food consumption, temporal preference (now vs. delayed consumption), and ratings of appetite and hunger were employed immediately before, immediately after, and 30 min after completion of the EX/R task. Questionnaires provided visual cues of hypothetical food items to assess preferences for different portion sizes as well as binary choices between food items with varying fat content and sweetness. Results: There were main condition effects for exercise both immediately ( P  = 0.02) and 30 min after the task ( P  = 0.004), demonstrating that EX resulted in increased prospective food consumption for immediate consumption (after task: 41.2 ± 90.7 kcal (EX) vs. 16.0 ± 74.2 kcal (R); 30 min after task: 78.7 ± 107.6 kcal (EX) vs. 46.6 ± 85.2 kcal (R)) and delayed consumption (after task: 10.5 ± 85. 9 kcal (EX) vs. −0.5 ± 73.6 kcal (R); 30 min after task (16.0 ± 88.2 kcal (EX) vs. −4.1 ± 95.2 kcal (R)). Fat content and sweetness did not impact prospective consumption immediately (both P  > 0.32) or 30 min after the task (both P  > 0.11). Exercise further resulted in an increased preference for immediate vs. delayed consumption both immediately ( P  = 0.02) and 30 min after the task ( P  = 0.02). Conclusions: Our findings indicate that exercise acutely shifts food choices towards greater amounts and a preference for more immediate food consumption, highlighting the importance of the timing of food choices in the context of exercise. Funding Sources: This work was funded by a Food for Health Collaboration Initiative grant by the University of Nebraska.